A Review and Evaluation of Prominent Theories of Writing - Holli R. Leggette; Tracy Rutherford; Deborah Dunsford; Lori Costello (Journal of Applied Communications, 2015)
Theoretical frameworks bring order to phenomena and provide a context for both research and practice. However, it has only been in the last four decades that theoretical frameworks have guided writing research. Before the 1980s, writing research focused more on mechanics and grammar than on cognitive thought processes related to writing. During the mid-1990s, theories shifted to a more sociocultural view of writing. Therefore, the purpose of this study was to apply theory evaluation criteria to theories of writing to review and evaluate their use and applicability in modern-day writing research. A literature review yielded three theories consistent across publications: cognitive process theory of writing, social cognitive theory of writing, and sociocultural theory of writing. The theories were reviewed and evaluated using accuracy, consistency, fruitfulness, simplicity/complexity, scope, acceptability, and sociocultural utility. Since the 1980s, writing researchers have modif ied theories to define writing ideas, concepts, and relationships. Cognitive processes should also be included in writing theories because of their importance in knowledge construction. Of the three theories that were reviewed and evaluated, the social cognitive theory of writing was the most complete. Its structure included society’s influence on writing and the cognitive processes involved in writing development. Each writing theory brought a unique perspective to writing research, but Flower’s theory was a complete theory that incorporated an in-depth look at writing as a product of cognitive processes situated within society. However, more research needs to be done on its applicability in agricultural communications research and practice.
Keywords: writing; evaluation; theories of writing